Efektivitas Pembelajaran Fikih dengan Menggunakan Kitab Kuning di MAS Al-Washliyah 1 Medan Area dan Madrasah Aliyah MualliminUniva - Br. Rambe, Siti Aisyah; Mardianto, Mardianto; Mahariah, Mahariah (Kamaya: Jurnal Ilmu Agama, 2025)
The implementation of yellow books in the education curriculum can be problematic when an institution does not prioritize the quality of learning from the book. Research on the problem of yellow books is important to do considering its relevance to learning methods that emphasize mastery of foreign languages ​​and in-depth study of material directly from primary sources. Based on field observations, several significant obstacles were found: low active participation of students in the process of learning yellow books which has an impact on decreasing their motivation to study fiqh through this medium, minimal understanding of students on the basic sciences for studying yellow books, namely nahwu and shorof, the dominance of traditional learning approaches such as memorization and lecture methods that do not accommodate contemporary learning styles. The purpose of this study was to determine the effectiveness of fiqh learning using yellow books at MAS Al-Washliyah 1 Medan Area and Madrasah Aliyah Muallimin Univa.This study uses a qualitative-analytical method. This method aims to examine in depth various phenomena experienced by the research object as a whole, such as behavioral patterns, perspectives, motivation to act, and other aspects. The study was conducted through analysis using systematic and structured language, paying attention to certain natural contexts and using various natural methods. The implementation of fiqh learning with yellow books at MAS Al-Washliyah 1 Medan Area and MA Muallimin UNIVA Medan is guided by the Al-Jamiatul Al-Washliyah curriculum. This curriculum was prepared by the Al-Jamiatul Al-Washliyah Executive Board and stipulates ten religious subjects using yellow books, including fiqh lessons. For fiqh subjects, both madrasas use the book “Minhajjul Thalibin” written by Imam An-Nawawi. This book is used for all levels from class X to class XII with a systematic division of material.